Improving ION/IOFF and sub-threshold swing in graphene nanoribbon field-effect transistors using single vacancy defects. (October 2015) - Nazari, Atefeh; Faez, Rahim; Shamloo, Hassan
Graphical abstract: Highlights: A graphene nanoribbon field effect transistor (GNRFET) with n-type source and drain and intrinsic channel is studied. Real-space Non-Equilibrium Green Function (NEGF) formalism is used. The effect of single vacancy (SV) defect on transistor performance is examined. The 3SVsGNRFET has higher on-current to off-current ratio and lower sub-threshold swing than 1SVGNRFET. Abstract: Graphene nanoribbon field effect transistors are promising devices for beyond-CMOS nanoelectronics. Graphene is a semiconductor material with zero bandgap and its bandgap must be changed. One of the opening bandgap methods is using graphene nanoribbons. By applying a defect, there is more increase on band gap of monolayer armchair graphene nanoribbon field effect transistor. So, by applying more than one defect, we can reach to much more increase in bandgap of graphene nanoribbon field effect transistors (GNRFET). In this paper, double-gated monolayer armchair graphene nanoribbon field effect transistors (GNRFET) with one single vacancy (1SV) defect (so-called 1SVGNRFET)are simulated and after changing positions of defect in width and length of channel of GNRFET, a structure with three single vacancy (3SVs) defects(so-called 3SVsGNRFET) is offered that this structure has higher I ON / I OFF ratio and lower sub-threshold swing than 1SVGNRFET and therefore has better performance. The energy band structure of nanoribbon is obtained by using nearest–neighbour interactions within an approximation tight binding model. Transfer characteristic of the transistor is simulated with solving Poisson-Schrodinger equation self-consistently by using Non- Equilibrium Green Function (NEGF) and in the real space approach.